Microscale Technologies for Cell Engineering - Singh, Ankur; Gaharwar, Akhilesh K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book offers readers cutting-edge research at the interface of polymer science and engineering, biomedical engineering, materials science, and biology. State-of-the-art developments in microscale technologies for cell engineering applications are covered, including technologies relevant to both pluripotent and adult stem cells, the immune system, and somatic cells of the animal and human origin. This book bridges the gap in the understanding of engineering biology at multiple length scale, including microenvironmental control, bioprocessing, and tissue engineering in the areas of cardiac, cartilage, skeletal, and vascular tissues, among others. This book also discusses unique, emerging areas of micropatterning and three-dimensional printing models of cellular engineering, and contributes to the better understanding of the role of biophysical factors in determining the cell fate. Microscale Technologies for Cell Engineering is valuable for bioengineers, biomaterial scientists, tissue engineers, clinicians, immunoengineers, immunologists and stem cell biologists, as it offers a review of the current cutting-edge cell engineering research at multiple length scale and will be valuable in developing new strategies for efficient scale-up and clinical translation.
From the contents : Introduction -- Part I: Microscale Technologies for Controlling Stem Cell Microenvironments -- Microscale culture of pluripotent stem cells -- Microscale technology in cellular reprogramming -- Microfluidics-based technologies for stem cells and embryos.Part II: Microscale Tissue Engineering using Stem Cells -- Spatially defined cell culture within three-dimensional hydrogels -- Combinatorial 3D Matrices for Human Embryonic Stem Cell Differentiation -- Engineered stem cell-based scaffolds and patches for heart disorders.
Keywords: Microtechnology; Microelectromechanical systems; Biomedical engineering; Stem cells; Microsystems and MEMS; Biomedical Engineering and Bioengineering; Stem Cell Biology